The Influence of Work Discipline and Organizational Culture on Employee Performance with Job Satisfaction as an Intervening Variable - Robby Dharma; Hamdy Hady; Lusiana; Muhammad Ridwan; Sitti Rizki Mulyani (Universitas Pendidikan Ganesha, 2023)
This research is motivated by the importance of understanding the relationship between company culture, work discipline, and employee job satisfaction in improving job performance. The main objective of this study was to investigate the impact of organizational culture and work discipline on employee job satisfaction levels, as well as test whether job satisfaction plays a mediator in the relationship between work discipline and employee work performance. This type of research is quantitative research with a descriptive approach. The population of this study consisted of all employees at PT. Bank Nagari West Sumatra, and the sample involved in this study amounted to 323 employees. Data collection was carried out using questionnaires as instrumentation. The results showed a positive relationship between organizational culture and employee job satisfaction levels. Work discipline is also positively related to employee job satisfaction levels, with job satisfaction acting as a mediator in the relationship. It was also found that organizational culture has a positive impact on employee performance. Furthermore, work discipline is also positively related to employee work performance. Success in creating a positive organizational culture and encouraging work discipline in the work environment can improve job satisfaction and overall employee performance. The conclusion of this study is the importance of the role of organizational culture and work discipline in increasing job satisfaction and employee performance at PT. Bank Nagari West Sumatra.